Triflic Anhydride Mediated Ring-Opening/Recyclization Reaction of α-Carbamoyl α-Oximyl Cyclopropanes with DMF: Synthetic Route to 5-Aminoisoxazoles - Yu, Mangfei; Zhang, Qian; Wang, Jia; Huang, Peng; Yan, Pengfei; Zhang, Rui; Dong, Dewen (Synthesis, 2016)
A facile and efficient synthesis of fully substituted 5-aminoisoxazoles was developed from α-cyclopropyl β-oximyl amides in the presence of triflic anhydride (Tf2O) in DMF under very mild conditions. The process involves sequential ring-opening and intramolecular cyclization reactions.
Keywords: cyclization; heterocycles; isoxazoles; ring-opening reaction